Indonesian Journal Of Social Work Volume 6 Number 2 February 2023: COPING STRATEGI KORBAN PENYALAHGUNAAN NAPZA PEREMPUAN DALAM MENGHADAPI HIGH RISK SITUATION PADA IPWL DI JAWA BARAT - Yulianti Suyono, Sinta; Ismudiyati, Yuti Sri; Rahayuningsih , Eni (Indonesian Journal of Social Work, 2023)
For drug users, returning to being a “normal” person is a struggling process. There is a High-Risk Situation that can cause the recovery process (abstinence) for drug users not to reuse. The ability to deal with various difficult situations or events, both personal demands (internal) and community demands (external) can cause pressure on a person. But whether an event will cause pressure or not, depends on how the individual handles it, which is called coping. This study aims to determine the Coping Strategy of female drug abusers in confronting High-Risk Situations at IPWL in West Java and to design programs to improve drug abusers of women’s coping capabilities. The method used in this research is quantitative with a descriptive approach. The results showed that of drug abuse of female in dealing with situations related to feelings faced by both negative and positive emotions tend to do Coping Strategy: Emotional Focus Coping (EFC), where they follow what is being felt. If the negative emotions are being felt, they will lost in these feelings which allows them to do things that can trigger a relapse or can hinder the rehabilitation process that is being carried out. Likewise, when faced with positive emotional situations, they also tend to enjoy the joy they feel so that their behavior is less controlled. Based on this, it is necessary for social workers and addiction counselors at IPWL to pay attention to mentoring drug abusers when they face situations related to emotional aspects. So that of drug abuse can choose effective coping strategies and rehabilitation goals can be achieved.